Blood Flow Restriction Does Not Promote Additional Effects on Muscle Adaptations When Combined With High-Load Resistance Training Regardless of Blood Flow Restriction Protocol. Issue 5 (May 2021) - Teixeira, Emerson Luiz; Ugrinowitsch, Carlos; de Salles Painelli, Vitor; Silva-Batista, Carla; Aihara, André Yui; Cardoso, Fabiano Nassar; Roschel, Hamilton; Tricoli, Valmor
Abstract : Abstract: Teixeira, EL, Ugrinowitsch, C, de Salles Painelli, V, Silva-Batista, C, Aihara, AY, Cardoso, FN, Roschel, H, and Tricoli, V. Blood flow restriction does not promote additional effects on muscle adaptations when combined with high-load resistance training regardless of blood flow restriction protocol. J Strength Cond Res 35(5): 1194–1200, 2021—The aim of this study was to investigate, during high-load resistance training (HL-RT), the effect of blood flow restriction (BFR) applied during rest intervals (BFR-I) and muscle contractions (BFR-C) compared with HL-RT alone (no BFR), on maximum voluntary isometric contraction (MVIC), maximum dynamic strength (one repetition maximum [1RM]), quadriceps cross-sectional area (QCSA), blood lactate concentration ([La]), and root mean square of the surface electromyography (RMS-EMG) responses. Forty-nine healthy and untrained men (25 ± 6.2 years, 178.1 ± 5.3 cm and 78.8 ± 11.6 kg) trained twice per week, for 8 weeks. One leg of each subject performed HL-RT without BFR (HL-RT), whereas the contralateral leg was randomly allocated to 1 of 2 unilateral knee extension protocols: BFR-I or BFR-C (for all protocols, 3 × 8 repetitions, 70% 1RM). Maximum voluntary isometric contraction, 1RM, QCSA, and acute changes in [La] and RMS-EMG were assessed before and after training. The measurement of [La] and RMS-EMG was performed during the control sessions with the same relative load obtained after the 1RM test, before and after training. Similar increases in MVIC, 1RM, and QCSA were demonstrated among all conditions, with no significant difference between them. [La] increased for all protocols in pre-training and post-training, but it was higher for BFR-I compared with the remaining protocols. Increases in RMS-EMG occurred for all protocols in pre-training and post-training, with no significant difference between them. In conclusion, despite of a greater metabolic stress, BFR inclusion to HL-RT during rest intervals or muscle contraction did not promote any additive effect on muscle strength and hypertrophy.